PENGETAHUAN IBU BALITA DENGAN PEMANFAATAN BUKU KIA: a Literature Review - Jihan Sayyidina Putri; Oktadoni Saputra; Tetra Arya Saputra; Prambudi Rukmono (Yayasan Nusantara Hasana Berdikari, 2026)
Maternal knowledge plays a crucial role in monitoring growth and improving the health of under-five children. The Maternal and Child Health (MCH) handbook is an educational and recording tool designed to support optimal childcare practices. However, its utilization remains suboptimal despite high ownership rates. This study discusses the relationship between maternal knowledge and the utilization of the MCH handbook, as well as factors influencing its use. Findings indicate that mothers with higher levels of knowledge are more likely to actively use the handbook for child health monitoring. Therefore, continuous education and supportive interventions are essential to optimize the use of the MCH handbook in promoting child health and development. This study employed a literature review method by examining relevant scientific articles on mothers’ knowledge of toddlers and the utilization of the MCH handbook obtained from various national and international databases.